Asset/liability management of financial institutions : maximizing shareholder value through risk-conscious investing - Tilman, Leo M. (London : Euromoney institutional investor, 2003)
The first-ever definitive guide to Asset/Liability Management (ALM) across the spectrum of financial institutions, this book is essential in developing consistent frameworks for risk management. Leveraging the experience of 38 senior industry practitioners, it provides a unique and practical perspective on the practice of ALM.
Includes bibliographical references.
oif 13/02/15
Loan
Keywords: Asset-liability management; Financial institutions; Risk management